2019
DOI: 10.17718/tojde.601934
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Online Course Experience from Students’ Perspective: Readiness, Attitudes and Thoughts

Abstract: The purpose of the study was to reveal the effect of a course taken through distance education on students' readiness and attitudes. Sequential explanatory design method was used as a research method in which qualitative and quantitative measurements were used in the research. For the quantitative data, a single group pre-test/post-test design was used as an experimental model; for the qualitative data, open-ended questions were asked in order to elicit students' opinions following the experimental process. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…Various documents have identified design guidelines that refer to the structure of a course. Beckers, Dolmans and Van Merriënboer (2016), Cabi and Kalelioglu (2019) and Hammarlund, Nilsson and Gummesson (2015) highlighted constructive alignment -one of the essential principles of education -as a design guideline. They emphasised that the learning objectives, teaching and learning strategies and assessment activities should be aligned in a course.…”
Section: Course Structurementioning
confidence: 99%
See 3 more Smart Citations
“…Various documents have identified design guidelines that refer to the structure of a course. Beckers, Dolmans and Van Merriënboer (2016), Cabi and Kalelioglu (2019) and Hammarlund, Nilsson and Gummesson (2015) highlighted constructive alignment -one of the essential principles of education -as a design guideline. They emphasised that the learning objectives, teaching and learning strategies and assessment activities should be aligned in a course.…”
Section: Course Structurementioning
confidence: 99%
“…Resources are featured as an important aspect of course design. Resources should be used to promote authentic, meaningful learning (Firat et al 2016;Zhang et al 2010), for interaction (Cabi & Kalelioglu 2019), to provide access to information and expert knowledge (Holland 2019), and address the challenges of developing the processes of cognition (Zhang et al 2010). It is of utmost importance that resources are easily accessible and available to students (Bayrak & Akcam 2017;Cabi & Kalelioglu 2019), that there are sufficient resources available and that they are of a high quality (Cabi & Kalelioglu 2019;Holland 2019) and of a wide variety (Firat et al 2016).…”
Section: Resourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Students were apprehensive about the possible negative implication of virtual education on their learning outcomes. Cabi & Kalelioglu (2019) reported that student attitudes towards virtual learning was positive for the majority, while the minority were unfavourably disposed.…”
Section: Student Phobia For Virtual Learningmentioning
confidence: 99%